Prevalence of nomophobia and its impact among medical students at an institution in Andhra Pradesh during COVID: an online study - Rajyalakshmi, Sai Venkata; Singamsetty, Bhaskar (International Journal Of Community Medicine And Public Health, 2021)
Background: Nomophobia the fear of being out of mobile phone contact, which refers to the discomfort, anxiety, stress, nervousness and anguish caused by being out of mobile phone connect. Aim of the to focus on impact of COVID lockdown on students’ developmental lifestyles and to assess the student’s prediction towards development of nomophobia. The current study also aims to compare addictive internet/smartphone related behaviours, time spent on internet usage other than education and impact on sleep quality, academic performance before and during the coronavirus pandemic. Methods: A cross sectional study was conducted at Narayana medical college for a period of 4 months from May 2020 to August 2020. A predesigned, validated questionnaire was developed (google survey form) and answers were collected from 600 students and interns in total by sending the questionnaire by email to all the participants. The responses were analyzed by SPSS, version 22.0. Test results with p value less than 0.05 only were considered statistically significant. Results: In our study, prevalence of nomophobia was more in females (58.96%) than males (42.06%). Gaming was the most common cause of mobile phone usage (79.67%). Poor sleep quality and mobile phone dependence were highest in interns (85.33% and 68%). Variables tested in relation with academic performance were having statistically significant association with nomophobe score of 24. Conclusions: Publicizing the negative consequences, creating awareness and health education during admission to medical graduates will definitely provide a ray of hope of opt utilization of mobile phone and decrease the chances of mobile addiction.